Drug Nanoparticle Formulation Using Ascorbic Acid Derivatives. (29th March 2011) - Moribe, Kunikazu; Limwikrant, Waree; Higashi, Kenjirou; Yamamoto, Keiji
Abstract : Drug nanoparticle formulation using ascorbic acid derivatives and its therapeutic uses have recently been introduced. Hydrophilic ascorbic acid derivatives such as ascorbyl glycoside have been used not only as antioxidants but also as food and pharmaceutical excipients. In addition to drug solubilization, drug nanoparticle formation was observed using ascorbyl glycoside. Hydrophobic ascorbic acid derivatives such as ascorbyl mono- and di-n-alkyl fatty acid derivatives are used either as drugs or carrier components. Ascorbyl n-alkyl fatty acid derivatives have been formulated as antioxidants or anticancer drugs for nanoparticle formulations such as micelles, microemulsions, and liposomes. ASC-P vesicles called aspasomes are submicron-sized particles that can encapsulate hydrophilic drugs. Several transdermal and injectable formulations of ascorbyl n-alkyl fatty acid derivatives were used, including ascorbyl palmitate.